CFD simulations of the mass transfer behavior of tar simulant on silicon oil in an absorber. (June 2022) - Jiang, Yanlong; Pan, Jiawei; Li, Danran; Zhang, Ni; Zhu, Bingbing; Jiang, Yichen; Chen, Haijun; Zhu, Yuezhao
Abstract: Oil washing for tar removal had achieved considerable success. However, hardly any research focused on the exploration of mass transfer in the tar absorber, especially due to viscosity. Mass transfer performance was simulated adopting phenol as tar simulant, and silicone oil as the absorbent. Transforming the physical parameters through COSMO. The results show that by adjusting the strengthening factor E to 1.1, compared with the experimental results, the maximum error was 12.93%, which was within the allowable engineering range. The viscosity has a greater influence on the mass transfer coefficient with a μ power of - 0.28, which deviates from the traditional Onda formula. The actual liquid-gas ratio of the system is 2.12 times of the minimum liquid-gas ratio, indicating a lower separation performance. When the porosity is 0.95, the removal efficiency can reach 99.9%, with an acceptable pressure drop. The atomizing nozzle angle being 20 grad, the height of mass transfer layer accounts for more than 2/3 of that of the tower, providing a removal efficiency up to 96.5%. The spraying speed of 6 m·s −1 is more preferred for a uniform flow and a high removal effect. Graphical abstract: Image 1